The Gorontalo Provincial Tourism Office's Strategy for Developing the Botubarani Whale Shark Geosite Towards a National Geopark - Rahmawaty A. Bayahu; Anggraeni M.S Lagalo; Desrika Talib (Tulisan Ilmiah Pariwisata (TULIP), 2026)
This study examines the development strategy of the Gorontalo Provincial Tourism Office in managing the Botubarani Whale Shark Geosite as part of efforts to support Gorontalo’s geopark development. Although Gorontalo has 13 identified potential geosites, this research focuses on Botubarani because it has distinctive biodiversity value through the presence of whale sharks and faces specific problems related to management, accessibility, facilities, tourism services, and the unpredictability of whale shark appearances. A descriptive qualitative approach was employed. Data were collected through observation, documentation, and structured interviews with four informants, namely representatives of the Gorontalo Provincial Tourism Office, Bappeda of Gorontalo Province, and the Botubarani Village Government. The data were analyzed using SWOT analysis through the identification of internal factors, including strengths and weaknesses, and external factors, including opportunities and threats. The results show that the Botubarani geosite is positioned in Quadrant I, indicating an aggressive SO strategy. Therefore, development should prioritize the use of local strengths and opportunities, including community participation, marine resources, educational tourism potential, and government support, while reducing weaknesses and threats that may affect destination sustainability.